2005
DOI: 10.1038/sj.bmt.1705142
|View full text |Cite
|
Sign up to set email alerts
|

Successful unrelated umbilical cord blood transplantation in children with Shwachman-Diamond syndrome

Abstract: Summary:Shwachman-Diamond syndrome (SDS) is an autosomal recessive disorder characterized by pancreatic insufficiency and variable degrees of neutropenia. SDS patients are at risk of developing myelodysplasia, aplastic anemia, and leukemic transformation. The role and timing of allogeneic hematopoietic stem cell transplantation (HSCT) in SDS remain controversial. We report three SDS patients with severe aplasia transplanted using unrelated umbilical cord blood (UCB). Patients received melphalan (180 mg/m 2 ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…More recently, a single report described three patients transplanted with UCB. 15 Unfortunately, long-term outcome data are not available for most of the patients. At the time of reporting, o50% of cases were noted to be alive.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a single report described three patients transplanted with UCB. 15 Unfortunately, long-term outcome data are not available for most of the patients. At the time of reporting, o50% of cases were noted to be alive.…”
Section: Discussionmentioning
confidence: 99%
“…The available literature on HSCT in SDS patients is limited and consists mainly of case reports. [19][20][21][22][23][24][25][26][27][28][29] Vibhakar et al 30 recently reviewed the published experience with HSCT in SDS patients and reported a total of 28 patients, including their own. All but four patients received ablative conditioning regimens containing CY with or without TBI/ TLI.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] The terminology non-malignant SC was preferred to aplastic anemia, because routine bone marrow samples from SDS patients exhibited dysgranulopoietic features or abnormalities of granulopoietic maturation. As in Fanconi anemia, the dyserythropoiesis, hyposegmentation or condensed chromatin should not be considered as a sign of myelodysplasia, 37 unless it is observed in more than 50% of the neutrophils.…”
Section: Discussionmentioning
confidence: 99%